Eskwela Kanlungan the redevelopment of CMIS-Sto Rosario to a school-emergency evacuation shelter - Allapitan, Princess Dorothy C. (College of Architecture, University of the Philippines Diliman, 2020)
This thesis seeks to create an educational environment that can be converted into an emergency evacuation shelter and that can encourage the learning process by addressing the issues of the new k-12 education system and integrating disaster risk resilient design. The concept implies that success in learning and teaching can be linked to the comfortability and flexibility of the learning spaces. Comfortability deals with how the students find their school as their comfort zone, a home, rather than an institution. Flexibility of an educational facility deals with how it adapts to the changes of the learning systems and as well as the changes in its environment. By integrating these design characteristics, the school can deal with both the issues on educational and environmental changes.